Immune cells as messengers from the CNS to the periphery: the role of the meningeal lymphatic system in immune cell migration from the CNS - Laaker, Collin; Baenen, Cameron; Kovács, Kristóf G.; Sandor, Matyas; Fabry, Zsuzsanna (Frontiers in Immunology, 2023)
In recent decades there has been a large focus on understanding the mechanisms of peripheral immune cell infiltration into the central nervous system (CNS) in neuroinflammatory diseases. This intense research led to several immunomodulatory therapies to attempt to regulate immune cell infiltration at the blood brain barrier (BBB), the choroid plexus (ChP) epithelium, and the glial barrier. The fate of these infiltrating immune cells depends on both the neuroinflammatory environment and their type-specific interactions with innate cells of the CNS. Although the fate of the majority of tissue infiltrating immune cells is death, a percentage of these cells could become tissue resident immune cells. Additionally, key populations of immune cells can possess the ability to "drain" out of the CNS and act as messengers reporting signals from the CNS toward peripheral lymphatics. Recent data supports that the meningeal lymphatic system is involved not just in fluid homeostatic functions in the CNS but also in facilitating immune cell migration, most notably dendritic cell migration from the CNS to the meningeal borders and to the draining cervical lymph nodes. Similar to the peripheral sites, draining immune cells from the CNS during neuroinflammation have the potential to coordinate immunity in the lymph nodes and thus influence disease. Here in this review, we will evaluate evidence of immune cell drainage from the brain via the meningeal lymphatics and establish the importance of this in animal models and humans. We will discuss how targeting immune cells at sites like the meningeal lymphatics could provide a new mechanism to better provide treatment for a variety of neurological conditions.